2022
DOI: 10.3389/feart.2022.940301
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Provenance of Early to Late Triassic Clastic Rocks From the Northwestern Sichuan Basin, Southwestern China: Constraints on the Early Mesozoic Tectonic Evolution of the Western Yangtze Block

Abstract: U–Pb ages of 637 new detrital zircons of Triassic sandstones from the Northwestern Sichuan Basin (NWSB), together with the petrology and paleocurrent data, are used to constrain the sediment provenance and tectonic–paleogeographic evolution of the western Yangtze Block. The U–Pb age data for the Lower Triassic detrital zircons generally show populations at ∼1,850 Ma, 980–705 Ma, 680–510 Ma, and 290–230 Ma with a minor cluster at ∼2.4 Ga. Such age spectrum features together with the eastward to northeastward pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…The detrital zircon age spectrum of the Early Triassic Feixianguan Formation is samilar to those of the cotemporary clastic sediments in the northwestern Sichuan Basin and Zigui Basin 12 , 41 , and all shows the major peaks at ~ 2500 Ma, ~ 1850 Ma and ~ 850 Ma. This age peaks are consistent with the episodes of magmatic activities in the South China Block 42 , 43 .…”
Section: Discussionmentioning
confidence: 57%
“…The detrital zircon age spectrum of the Early Triassic Feixianguan Formation is samilar to those of the cotemporary clastic sediments in the northwestern Sichuan Basin and Zigui Basin 12 , 41 , and all shows the major peaks at ~ 2500 Ma, ~ 1850 Ma and ~ 850 Ma. This age peaks are consistent with the episodes of magmatic activities in the South China Block 42 , 43 .…”
Section: Discussionmentioning
confidence: 57%
“…The gravel and sandstone found in the northern Jianghan Basin document the unroofing history of the South Qinling Shan during the Early Jurassic [40,69] (Figure 4b; Figure 7(5)). At the same time, previous studies have demonstrated the U-Pb provenance tracing results of detrital zircon, which indicate that the South Qinling Shan served as a stable provenance area in the northern Sichuan Basin during the Early Jurassic [39,70,71] (Figure 7(6)). The unannealed zircon fission-track and zircon (U-Th)/He ages obtained from these formations in the northern Sichuan Basin indicate that the exhumation of the South Qinling Shan occurred between 196 and 180 Ma [66,72] (Figure 7(7,8)).…”
Section: The Mesozoic Exhumationmentioning
confidence: 65%
“…This exhumation led to the formation of large rivers that flowed into the Jianghan Basin and Sichuan Basin on the east and west sides of the Huangling anticline, respectively [110,111]. The western (4) [39]; (5) [40,67]; (6) [39,70,71]; (7) [65]; (8) [72]; (9) [41,73]; (10) [74]; (11) [75]; (12) This study; (13) [28]; (14) [7,8,[76][77][78]; (15) [67]; (16) [79]; (17) [80]; (18) [81]; (19) [74]; (20) [82]; (21) [70]; (22) [83]; (23) [84]; (24)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations